Implementasi Pendidikan Literasi Ekonomi pada Jenjang Sekolah Dasar yang Berbasis Bahan Ajar Tematik di UPT SPF SD Inpres Perumnas - Pabisi, Sri Udayanti; *, Elpisah; Rahman, Nawir; Rismawanti, Erni (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Research objectives: 1) To find out how the implementation of economic literacy education for students based on thematic teaching materials at UPT SPF SD Inpres Perumnas Makassar City, 2) To find out what factors have an impact on the implementation of economic literacy education for students based on UPT thematic teaching materials SPF SD Inpres Perumnas Makassar City. This research uses descriptive qualitative research. This data collection technique uses an interview guide which was distributed to the sources for this research, namely school principals, teachers and students, as well as parents at UPT SPF SD Inpres Perumas Makassar. Results of this research 1). Implementation of economic literacy education at elementary school level based on thematic teaching materials delivered by teachers to make it easier for students to understand the material presented by the teacher, because if you only use the handbook that has been provided by the school, the material obtained will not be understood by students. 2) Factors in implementing economic literacy based on thematic teaching materials via audio using audio in the form of mini speakers in material about formulas in economics to make it easier for teachers to convey the material to students. 3) Implementation factors of economic literacy based on thematic teaching materials via audio-visual using audio-visual teaching materials in the form of a computer and assisted by loudspeakers on economic theory material.